2005
DOI: 10.1086/428347
|View full text |Cite
|
Sign up to set email alerts
|

Deflection of Pulsar Signal Reveals Compact Structures in the Galaxy

Abstract: We have detected a strong deflection of radio waves from the pulsar PSR B0834ϩ06 in scintillation observations. Interference between the undeflected pulsar image and deflected subimages allows single-dish interferometry of the interstellar medium with submilliarcsecond resolution. We infer the presence of scattering structure(s) similar to those that are thought to cause extreme scattering events in quasar flux monitoring programs: size ∼0.2 AU (an angular size of 0.1 mas) with an electron overdensity of տ10 3… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

22
93
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 91 publications
(116 citation statements)
references
References 20 publications
(45 reference statements)
22
93
0
Order By: Relevance
“…However, the clumps are small enough that they produce effectively no additional broadening. This scenario is also broadly consistent with the notion of clumps of material producing extreme scattering events (Fiedler et al 1987) and parabolic arcs in pulsar dynamic spectra ( Hill et al 2005).…”
Section: Discussionsupporting
confidence: 87%
“…However, the clumps are small enough that they produce effectively no additional broadening. This scenario is also broadly consistent with the notion of clumps of material producing extreme scattering events (Fiedler et al 1987) and parabolic arcs in pulsar dynamic spectra ( Hill et al 2005).…”
Section: Discussionsupporting
confidence: 87%
“…First recognized by Stinebring et al (2001) in Arecibo data, detailed studies of these arcs have revealed a variety and richness in their observational manifestations; e.g., forward and reverse arcs, and a chain of arclets (Hill et al 2005;Putney & Stinebring 2006;Brisken et al 2010), which also stimulated a great deal of theoretical and modeling work (Walker et al 2004;Cordes et al 2006;Brisken et al 2010). In the context of PTAs Hemberger & Stinebring (2008) measured scattering delays from their observations of scintillation arcs in PSR B1737+13 (DM=48.9 pc cm 3 -); the delays varied from ∼0.2 to 2 μs at a frequency of 1.3 GHz.…”
Section: Introductionmentioning
confidence: 99%
“…A representative secondary spectrum is shown in the top panel of Figure 1. The power in the secondary spectrum is distributed along a parabolic scintillation arc (Stinebring et al 2001;Hill et al 2003Hill et al , 2005Walker et al 2004;Cordes et al 2006). This is the transform domain representation of the crisscross pattern often seen in dynamic spectra, and it arises from interference between central and peripheral rays of the scattered image (Stinebring et al 2001;Cordes et al 2006).…”
Section: Observationsmentioning
confidence: 99%